2010
DOI: 10.1128/aac.00411-10
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Therapy with Colistin Methanesulfonate: a Biopharmaceutical Issue Illustrated in Rats

Abstract: The aim of this study was to evaluate the biopharmaceutical behavior of colistin methanesulfonate (CMS) with special focus on colistin presystemic formation after CMS nebulization in rats. CMS was administered (15 mg ⅐ kg ؊1 of body weight) either intravenously for systemic pharmacokinetic studies (n ‫؍‬ 6) or as an intratracheal nebulization for systemic pharmacokinetic studies (n ‫؍‬ 5) or for CMS and colistin concentration measurements in epithelial lining fluid (ELF) at 30, 120, and 240 min after nebulizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
85
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 29 publications
10
85
3
2
Order By: Relevance
“…Following the nebulization of sodium CMS (15 mg/kg of body weight) in rats, a ϳ4-fold-higher plasma concentration-versus-time exposure was observed for formed colistin compared to i.v. administration of the same CMS dose (39). We recently reported similar observations in rats where the intratracheal method resulted in formed colistin exposure in ELF that was 8,000-fold higher than that in plasma after i.v.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Following the nebulization of sodium CMS (15 mg/kg of body weight) in rats, a ϳ4-fold-higher plasma concentration-versus-time exposure was observed for formed colistin compared to i.v. administration of the same CMS dose (39). We recently reported similar observations in rats where the intratracheal method resulted in formed colistin exposure in ELF that was 8,000-fold higher than that in plasma after i.v.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast to the low systemic availability of CMS and formed colistin (Ͻ2 to 3% of the nebulized CMS dose recovered in urine) observed in CF subjects in the current study, Marchand et al (39) reported that the total dose of CMS administered by intratracheal nebulization to rats was absorbed into the systemic circulation either as CMS (systemic availability of ϳ70%) or following CMS conversion to colistin in the lungs (39% of the nebulized CMS dose). Following the nebulization of sodium CMS (15 mg/kg of body weight) in rats, a ϳ4-fold-higher plasma concentration-versus-time exposure was observed for formed colistin compared to i.v.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…The intraday and interday variabilities in plasma and BAL fluid were determined at three concentrations with a precision and accuracy of Ͻ15%. Concentrations of urea in plasma and BAL fluid were measured as previously described (7). TOB concentrations in epithelial lining fluid (C ELF ) were derived from measured TOB concentrations in BAL fluid (C BAL ) after correction by urea dilution (7).…”
mentioning
confidence: 99%
“…Concentrations of urea in plasma and BAL fluid were measured as previously described (7). TOB concentrations in epithelial lining fluid (C ELF ) were derived from measured TOB concentrations in BAL fluid (C BAL ) after correction by urea dilution (7). TOB concentrations in plasma and ELF versus time were simultaneously analyzed by a nonlinear mixed-effects method with S-ADAPT software (v 1.52), and the final structural PK model was derived from previous studies (2, 3).…”
mentioning
confidence: 99%